Synthesis and Characterization of Coordination Polymers Constructed From [ZnII, CdII]-2, 2’-Dipyridine and Bipyhenyl-4, 4’-Dicarboxylic Acid - Yadav, Pramod Kumar (Journal of Nepal Chemical Society, 2017)
Available with fulltext.